The Role of the Level of Interleukin-33 in the Therapeutic Outcomes of Immunotherapy in Patients with Allergic Rhinitis - Nasr,Wail Fayez (2018)
Abstract Introduction Allergic rhinitis (AR) affects up to 40% of the population and results in nasal itching, congestion, sneezing, and clear rhinorrhea. Objectives This study aimed to evaluate the changes in the clinical symptoms and in the level of serum interleukin (IL)-33 before and after pollen immunotherapy (IT) in patients with AR. Methods The total symptomscore and the levels of total immunoglobulin E (IgE) and IL-33 were determined in the serum of 10 non-allergic healthy controls and 45 patients with AR who were equally divided into 3 groups: GI (patients did not receive IT), GII (patients had received IT for 6 months) and GIII (patients had received IT for 2 years). Results There was a significantly higher concentration of IgE and IL-33 in the serum of patients with AR than in that of non-allergic patients. Furthermore, serum level of IL-33 decreased significantly after pollen IT. But, there was no significant reduction in the serum level of IL-33 between GII and GIII patients. Conclusion Our results show a clinical improvement associated with a decrease in serum level of IL-33 after pollen IT.